Pengaruh Eksistensi Bandara International Lombok Terhadap Perkembangan Permukiman di PKW Perkotaan Praya - Haryono, Yuswan (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2016)
Inequality development causes delays for Praya development. MP3EI, changed conditions of Urban Praya through the construction of Lombok International Airport (BIL) that is represented as Regional Activity Center. The development began to grow including the settlements sector. The purpose of this study is to assess the effect of the presence of BIL on the development of settlements in Praya urban with quantitative descriptive method; through the identification residential development from the aspects existence of BIL, pattern and shape of its range, physical and non-physical variables that affect and changes pattern and Structures space. The results showed, the development of urban settlements do not occurs due to the direct presence of BIL but influenced by the roads and utility networks. Praya urban image map in 2006 and 2012 showing the development of settlement that is shaped "Radial Continuous" and other territories form Praya urban scattered "Linear" following the road and utility grid, whereas the other territories near BIL does not show a significant development. According to the Patterns of change and Structure Space, the land price changes. The suburban area of Praya that is experiencing the development of road, the land prices have increased despite relatively less productive land.